COLD CALLING IN THE DEVELOPMENT OF THE MARKETPLACE TO PURCHASE DECISIONS FOR FOOD AND BEVERAGE PRODUCTS IN YOGYAKARTA - Aditya Pratama; Sukardi (Jurnal Ekonomi, 2022)
This research is motivated by the development of marketing technology for today's food and beverage products. This study aims to provide an overview of the most influential forms of marketing to be carried out during the development of Marketplace and E-commerce. This research is quantitative research, by distributing questionnaires to student respondents who are familiar with the current business phenomenon. The results showed that digital marketing and the use of word of mouth (WOM) had a positive and significant effect on purchasing decisions, while face-to-face selling and telemarketing had no significant effect on purchasing decisions. The application of changing promotional strategies from conventional to digital marketing has become a productive way of doing marketing because it has significant positive potential